Gambaran Kasus Gondongan Pada Sekolah Dasar Negeri 010 Makroman, Samarinda - Listiani, Dwi; Astuti, Ashri Budi; Jami'an, Jami'an; Budi, Eko Prasetya; Sumarianto, Arif; Pakki, Irfansyah Baharuddin (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Mumps is an infectious disease caused by a viral infection, often attacking the salivary glands, especially the parotid glands. This disease is self-limiting and common in elementary school children. This study aims to describe the prevalence, symptoms, and impact of mumps in students of SD Negeri 010 Makroman, Samarinda, as well as evaluate risk factors and relevant prevention efforts. With a descriptive research design, data was obtained from a population of 307 students through secondary data from the Makroman Health Center and direct on-site investigations. An attack rate of 3.58% indicates a limited impact on at-risk populations, but it is important to be aware of the potential for further transmission in the school environment. This study emphasizes the importance of preventive efforts, promotive measures, and continuous supervision These results provide insight for health policymakers to improve measures to prevent and control mumps in the school environment.